Consistency in climate change impact reports among indigenous peoples and local communities depends on site contexts - Schunko, C.; Álvarez-Fernández, S.; Benyei, P.; Calvet-Mir, L.; Junqueira, A. B.; Li, X.; Porcuna-Ferrer, A.; Schlingmann, A.; Attoh, Emmanuel M. N. A. N.; Carmona, R.; Chengula, F.; Fernández-Llamazares, Á.; et al. (Nature Portfolio, 2024)
Indigenous Peoples and local communities are heavily affected by climatic changes. Investigating local understandings of climate change impacts, and their patterned distribution, is essential to effectively support monitoring and adaptation strategies. In this study, we aimed to understand the consistency in climate change impact reports and factors influencing consistency at site and individual levels. We conducted cross-cultural research among iTaukei (Fiji), Dagomba (Ghana), fisherfolks (Tanzania), Tsimane’ (Bolivia), Bassari (Senegal), ribeirinhos (Brazil), Mapuche (Chile), Mongolian (China), Tibetan (China) and Daasanach (Kenya) communities using semi-structured interviews, focus groups, and surveys among 1860 individuals. We found that cross-culturally more than two-thirds of individual reports of climate change impacts match site-confirmed reports. Consistency in reports is higher for changes related to pastoralism than crop production and wild plant gathering. Individual’s experience with nature, Indigenous and local knowledge, and local family roots are not significantly associated with consistency across sites, but site-specific associations are prevalent. Despite high average consistency among sites, there is considerable variation caused by site-specific factors, including livelihood activities, socio-cultural settings, and environmental conditions. Site contexts and related consistency in climate change impact reports need to be taken into account for climate change monitoring and adaptation planning.